Peroxisome proliferator‐activated receptor gamma (PPARγ) regulates lactase expression and activity in the gut - Mathurin Fumery; Silvia Speca; Audrey Langlois; Anne‐Marie Davila; Caroline Dubuquoy; Marta Grauso; Anthony Martin Mena; Martin Figeac; Daniel Metzger; Christel Rousseaux; Jean‐Frederic Colombel; Laurent Dubuquoy; et al. (EMBO Molecular Medicine)
Abstract Lactase (LCT) deficiency affects approximately 75% of the world's adult population and may lead to lactose malabsorption and intolerance. Currently, the regulation of LCT gene expression remains poorly known. Peroxisome proliferator activator receptorγ (PPARγ) is a key player in carbohydrate metabolism. While the intestine is essential for carbohydrate digestion and absorption, the role of PPARγ in enterocyte metabolic functions has been poorly investigated. This study aims at characterizing PPARγ target genes involved in intestinal metabolic functions. In microarray analysis, the LCT gene was the most upregulated by PPARγ agonists in Caco‐2 cells. We confirmed that PPARγ agonists were able to increase the expression and activity of LCT both in vitro and in vivo in the proximal small bowel of rodents. The functional response element activated by PPARγ was identified in the promoter of the human LCT gene. PPARγ modulation was able to improve symptoms induced by lactose‐enriched diet in weaned rats. Our results demonstrate that PPARγ regulates LCT expression, and suggest that modulating intestinal PPARγ activity might constitute a new therapeutic strategy for lactose malabsorption.